DFT-Based Study of the Intramolecular Interactions of Some Aminoglycosides - Makhadiyeva, K.Sh.; Abulyaissova, L..K.; Kasymova, M.S. (Karagandy University of the name of acad. E.A. Buketov, 2023)
The quantum chemical modeling and full geometry optimization of sisomicin and gentamicin were carried out by the correlation functional B3LYP using augmented with polarization functions for heavy atoms 6- 311G(d) and Dunning’s correlation consistent cc-pVDZ basis sets. The effect of the basis set on the calculation results of molecular structure and quantum chemical descriptors of the titled compounds was studied. Special attention was paid to the intramolecular NH…N, OH…N, OH…O, NH…O hydrogen bonds in sisomicin and gentamicin. According to theoretical calculations, the distances between hydrogen and acceptor atoms are a bit longer than a typical length due to a significant deviation of the intramolecular H-bonds from a linearity. To evaluate the extent of electron density delocalization from the lone pairs of atoms into the antibonding neighboring orbitals and inside H-bonds within the systems, NBO (Natural Bond Orbital) analysis was used at two levels of theory. The most intensive interactions between electron donor and electron acceptor in the structures under consideration are determined and their delocalization energies are evaluated. Based on the obtained data, classical electrostatic nature of the weak H-bonds and conjugation effects stabilizing the molecules are suggested.
Keywords: aminoglycoside antibiotics; sisomycin, gentamicin; DFT calculation; B3LYP; NBO analysis; hydrogen bond; delocalization energy